9-4b=6-5b

Simple and best practice solution for 9-4b=6-5b equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9-4b=6-5b equation:


Simplifying
9 + -4b = 6 + -5b

Solving
9 + -4b = 6 + -5b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '5b' to each side of the equation.
9 + -4b + 5b = 6 + -5b + 5b

Combine like terms: -4b + 5b = 1b
9 + 1b = 6 + -5b + 5b

Combine like terms: -5b + 5b = 0
9 + 1b = 6 + 0
9 + 1b = 6

Add '-9' to each side of the equation.
9 + -9 + 1b = 6 + -9

Combine like terms: 9 + -9 = 0
0 + 1b = 6 + -9
1b = 6 + -9

Combine like terms: 6 + -9 = -3
1b = -3

Divide each side by '1'.
b = -3

Simplifying
b = -3

See similar equations:

| 6-4(5+3y)=0 | | 8-1/2(-m-1) | | M+6=2m+11 | | 7v-15+7v=7v+48 | | 23=32x-425 | | 1680=336t | | 5(9x+6)=45x-4 | | 0.5x=-70 | | 3lx-1l=15 | | (3x+25)+(x-5)+x=180 | | -5-8=-13x-4 | | 2x+105=-3x+130 | | 7n+3=8+8n | | f(a+1)=(a+1)+8 | | a-43+a-43+w+43=a | | 9x+8=9x-2 | | 15*3-25+10= | | u+u+3=u+46 | | 3x-5(x-4)=-5+4x+13 | | 3x+9x-7=3(4x+4) | | 8t+40+16t-49=18t+23 | | 18x-12=3x^2 | | 7+6*2-2+8= | | 7a+21b=110 | | 2(1/6)*(3/26) | | d=85(4h) | | 34+32a-50=23a+26 | | 6x+6=6x+5 | | 2l+2w=98.2 | | 5-6y=35 | | -12720+200= | | 4/7x-1/3=1/5 |

Equations solver categories